Unleashing the potential of metaphors: a categorization system for exploring return to work after maternity - Rapisarda, Sebastiano; Santoro, Valentina; Dal Corso, Laura (Archives of women's mental health, 2024)
Purpose Return to work after maternity leave represents a radical change in women’s lives. This paper aims to present a new metaphor categorization system based on two studies, which could assist working mothers in expressing the nuances of their experience when returning to work after maternity leave. Methods We carried out the analysis of the metaphors according to the method for thematic analysis, through a multistep, iterative coding process. To ensure the researchers encode the data similarly, inter-coder reliability was achieved through the judges’ agreement method. The level of agreement between the two judges was measured by Cohen’s kappa. Results In Study 1, we established a system comprising ten metaphor categories (namely, Natural event and/or element, Challenge and destination, Movement and/or action, Fresh start, Fight, Game and hobby, Animal, Alternate reality, Means of transport, Hostile place). In Study 2, we recognized the same metaphor categories observed in Study 1, except “Means of transport”, even with data sourced from a distinct participant group, an indicator of credibility in terms of inter-coder reliability. Conclusion Findings highlight the usefulness of this new metaphor categorization system (named Meta4Moms@Work—Metaphors system for Moms back to Work) to facilitate a more straightforward elicitation of the meanings employed by working mothers to depict their return to work after maternity leave. Leveraging these insights, researchers/practitioners can develop and execute primary and secondary interventions aimed to enhance working mothers’ work-life balance, well-being, and mental health.